Optimal rate allocation for progressive fine granularity scalable video coding. - Qi Wang (IEEE Signal processing letters)
We examine the enhancement-layer rate allocation problem in progressive fine granularity scalable (PFGS) video coding. The problem arises from the fact that different frames in the enhancement layer have different rates in PFGS coding. A rate-distortion (R-D) function for a multiframe group is first established for enhancement-layer PFGS coding, followed by experiments to verify its validity using real test sequences. Optimal rate allocation among frames in the group is then given based on the R-D function, together with a simple implementation that is suitable for applications such as streaming video. Experiments show that, compared with uniform bit allocation, optimal bit allocation not only makes the quality variation in decoded video much smoother, but also improves the average PSNR of PFGS coding by 0.3-0.5 dB